EMOTIONAL REGULATION TECHNIQUES FOR MOOD DISORDER PATTERNS OF NARCOTICS INJECTORS IN PERSONALITY DEVELOPMENT ACTIVITIES AT CLASS IIA NARCOTICS CORRECTIONAL INSTITUTION, PEMATANG SIANTAR - Simanjuntak, Epriel Paruntungan; Simanjuntak, Meitisa Vanya (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2025)
Inside correctional institutions, drug inmates face not only the challenge of confinement but also the struggle to control their emotions and overcome the inner chaos caused by addiction. Each group of inmates, whether addicts, dealers, or users, shows unique emotional characteristics that require a specific and targeted approach in their rehabilitation process. This study aims to explore effective emotion regulation techniques to address different patterns of mood disorders among drug inmates at the Class IIA Pematang Siantar Narcotics Correctional Institution. Using a qualitative case study approach, data were collected through in-depth interviews, direct observations, and analysis of personality development program documents. The results showed that addicts experienced intense emotional fluctuations, dealers tended to display aggressive and manipulative behaviors, while users often suffered from depression and anxiety. The integration of emotion regulation techniques based on the model of James J. Gross into personality development programs proved effective in improving emotional stability and reducing symptoms of mood disorders. The study highlights that well-structured emotional regulation interventions can significantly enhance rehabilitation outcomes and lower the possibility of relapse among narcotics inmates, creating a more humane and sustainable correctional environment.